Response of Exposed Pulp to Capping with Mineral Trioxide Aggregate Mixed with Hyaluronic Acid as a Water Substitute - Muthanna S. Ahmed; Nadia H. Hasan; Mohammed G. Saeed; Aous A. Abdulmajeed (University of Mosul, College of Dentistry, 2024)
Aims: exposed pulp can be managed by Mineral trioxide aggregate (MTA) that stimulates reparative dentin deposition at the site of exposure. The study aims to evaluate the healing of exposed pulp immunohistochemically by using hyaluronic acid (HA) with MTA by evaluating collagen III expression rate. Materials and method: Ninety teeth were used from 10 dogs to perform an experimental pulp exposure. The samples were divided into three groups according to the mixing medium with MTA: group I: MTA + distilled water (control group), group II: MTA + hybrid cooperative complex hyaluronic acid (HCC-HA), group III: MTA + high molecular weight hyaluronic acid (HMW-HA). After pulp capping, all cavities were restored with glass ionomer restoration. The dogs were divided randomly into five groups (2 dogs each) according to the evaluation periods (7,14,21,30,60) days. At the end of the study, the dogs were euthanized and the sampled teeth were processed for immunohistochemical investigation to evaluate collagen III expression rate by Kruskal-Wallis Test using Pairwise Multiple Comparison Tukey Test with significant level set on P ≤ 0.05. Results: Both types of hyaluronic acid (HCC-HA, HMW-HA) showed a statistically higher expression rate of collagen III than using distilled water with MTA. Conclusions: within the limitations of this study, using HA for mixing with MTA increased collagen III expression, which can be explained as an increase in the healing process. HA could be an effective water substitute for mixing with MTA for direct pulp capping.